Effect of Green Tea Extract and Soy Isoflavones on the Pharmacokinetics of Rosuvastatin in Healthy Volunteers - Zeng, Weiwei; Hu, Miao; Lee, Hon Kit; Wat, Elaine; Lau, Clara Bik San; Ho, Chung Shun; Wong, Chun Kwok; Tomlinson, Brian (Frontiers in Nutrition, 2022)
Background and Aim: Green tea and soy products are extensively consumed in daily life. Research has shown that green tea catechins and soy isoflavones may influence the activity of drug metabolizing enzymes and drug transporters. We examined whether regular consumption of green tea extract or soy isoflavones affected the pharmacokinetics of a single dose of rosuvastatin in healthy subjects and whether any interactions were influenced by the polymorphism in the drug transporter ABCG2. Study Design: This was an open-label, three-phase randomized crossover study with single doses of rosuvastatin. Methods: Healthy Chinese male subjects were given a single dose of rosuvastatin 10 mg on 3 occasions: 1. without herbs; 2. with green tea extract; 3. with soy isoflavone extract. The green tea and soy isoflavone extract were given at a dose containing EGCG 800 mg once daily or soy isoflavones ~ 80 mg once daily for 14 days before statin dosing and at the same time as the statin dosing with at least 4-weeks washout period between phases. Results: Twenty healthy male subjects completed the study and the intake of green tea extract significantly reduced the systemic exposure to rosuvastatin by about 20% reducing AUC0-24h from [geometric mean (% coefficient of variation)] 108.7 (28.9) h‧µg/L to 74.1 (35.3) h‧µg/L and Cmax from 13.1 (32.2) µg/L to 7.9 (38.3) µg/L (P<0.001 for both), without affecting the elimination half-life. The ABCG2 421C>A polymorphism had a significant effect on rosuvastatin exposure but no impact on the interaction with green tea. Soy isoflavones had no significant effect on rosuvastatin pharmacokinetics. Conclusion: This study showed that repeated administration of green tea extract significantly reduced the systemic exposure of rosuvastatin in healthy volunteers. These effects might be predicted to either reduce or increase the lipid-lowering effect of rosuvastatin depending on the mechanism of the effect.